Multi-location trials identify stable high yielding spring bread and durum wheat cultivars in Mexico - Valenzuela Antelo, Jorge L.; Benítez-Riquelme, Ignacio; Vargas Hernández, Mateo; Huerta Espino, Julio; Bentley, Alison R.; Villaseñor Mir, Héctor Eduardo; Piñera Chavez, Francisco J. (Cold Spring Harbor Laboratory, 2023)
Determining the stability and consistency of grain yield performance requires accurate evaluation of genotypes in different environments. In Mexico, annual national spring wheat irrigated trials are conducted to assess elite bread and durum wheat performance in different testing environments (TEs) in the main wheat-growing areas. These trials provide data supporting release of new cultivars and aim to also address Mexican wheat value chain grain needs. In this study we analyzed 30 bread and durum wheat trial results from the 2012/13 and 2013/14 growing cycles conducted across TEs in northwest, north and central Mexico. Environmental variability (location, sowing timing, and irrigation schemes) across the national spring wheat irrigated trials enabled genotype by environment interaction to be effectively evaluated. We identified genotypes with high and stable grain yield across TEs of the wheat-growing areas of Mexico. The bread cultivars Bacorehuis F2015 and Borlaug100 F2014, and the durum cultivars Barobampo C2015, CONASIST C2015 and Anatoly C2011 were high yielding and gave stable performance in most of the TEs. This analysis demonstrates the utility of multi-year, multi-environment testing and analysis to identify improved wheat cultivars to meet wheat production demand in Mexico.